Ética radical e psicoterapia centrada na pessoa: uma investigação acerca da abertura à alteridade radical na relação terapêutica a partir de discursos de psicoterapeutas sobre o inusitado em sua prática clínica - Miranda, Carmen Silvia Nunes de (2012)
This study constitutes of a qualitative research with a descriptive and exploratory character. It intends to contribute to a discussion of ethics in clinical practice, with reference to the radical ethics of Emmanuel Levinas and the Person-Centered Psychotherapy. The overall goal is to understand the possibilities of opening to radical alterity in the therapeutic relationship from discourses of person-centered psychotherapists about their clinical practice. Thus, we performed semi-structured interviews with five psychotherapists about the unexpected experiences in their clinical practice. The interpretation of the discourses was inspired in Derrida's hermeneutics, focusing on how the idea of deconstruction was proposed, allowing the arising of the difference in speech itself. In the deconstruction of the discourses we get closer to potential areas of openness to otherness in the therapeutic relationship, talking about the therapist vulnerability and responsibility against the unexpected. In a welcoming position the therapist would have to allow the use of his sensitivity and the intuition in their attendance, being with the client in its suffering, from the facilitative attitudes as enablers of a understanding of the client as an enigma.